Ta’aruf Rules in Digital Room: Study of Matchmaking Process on Biro Jodoh Rumaysho Social Media - Handayani, Dwi Sri (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2022)
Abstract: This study examines the online taa'ruf process through social media that is run by the Biro Jodoh Rumaysho (BJR) and at the same time the reciprocal relationship between managers and participants. Basically, this is a field research, however, in extracting the data, it relies a lot on the internet, so this research can also be categorized as a netnographic study. The results of this study indicate that the Rumaysho Matchmaking Bureau has facilitated many people who want to find a life partner through the stages of ta'aruf. These services are carried out online through social media, such as Instagram, Facebook, and also the Website. The success rate of ta'aruf with this model is relatively high because it has been filtered based on the criteria desired by each potential partner. The ta'aruf process which is carried out in this way has led to a social phenomenon in society which makes ta'aruf a religious and also economic spirit, both for implementing agencies and participants where there is mutuality between the two.Abstrak: Penelitian ini mengkaji proses taa’ruf secara online yang dijalankan oleh Biro Jodoh Rumaysho dan sekaligus hubungan timbal balik antara pengelola dengan peserta. Pada dasarnya ini merupakan penelitian lapangan namun dalam penggalian datanya banyak bergantung pada internet sehingga penelitian ini juga bisa dikategorikan sebagai studi netnografi. Hasil dari penelitian ini menunjukkan bahwa Biro Jodoh Rumaysho telah banyak memfasilitasi masyarakat yang ingin mencari pasangan hidup melalui tahapan ta’aruf. Layanan tersebut dilakukan secara daring melalui media sosial, seperti Instagram, Facebook, dan juga Website. Tingkat keberhasilan ta’aruf dengan model ini relatif tinggi karena telah dilakukan penyaringan berdasarkan kriteria yang diinginkan oleh masing-masing calon pasangan. Proses ta’aruf yang dilakukan dengan cara demikian telah memunculkan fenomena sosial masyarakat yang menjadikan ta’aruf sebagai spirit keagamaan dan juga ekonomi, baik untuk lembaga pelaksana maupun peserta yang mana terjadi mutualan di antara keduanya.